Urinary angiotensinogen, related factors and clinical implications in normotensive autosomal dominant polycystic kidney disease patients. (June 2014) - Kurultak, Ilhan; Sengul, Sule; Kocak, Senem; Erdogmus, Siyar; Calayoglu, Reyhan; Mescigil, Pinar; Keven, Kenan; Erturk, Sehsuvar; Erbay, Bulent; Duman, Neval
Abstract Background: Although several lines of evidence suggest that renin angiotensin system (RAS) proteins are synthesized by cyst epithelium and dilated tubules, role of intrarenal RAS in the progression of otozomal dominant polycystic kidney disease (ADPKD) is not well known. We aimed to study the levels and clinical correlations of urinary angiotensinogen (UAGT) in normotensive ADPKD patients compared with age- and sex-matched healthy subjects. Methods: The study included 20 normotensive ADPKD patients (F/M: 11/9) and 20 age and sex matched healthy controls (F/M: 9/11). Diagnosis of ADPKD was made based on Ravine criteria. Twenty-four hours ambulatory blood pressure monitoring (ABPM) was performed. Serum concentrations of creatinine, Na, K, uric acid, and urinary concentrations of Na, K, uric acid, creatinine, protein and albumin were measured. UAGT were measured via commercially available ELISA kit. Results: ADPKD patients had higher urinary albumin:creatinine ratio (UAIb/UCrea) than healthy controls (p < 0.01). UAGT/UCrea levels significantly positively correlated with urinary protein: creatinine ratio (UPro/UCrea) (r = 0.785, p = 0.01), and UAIb/UCrea (r = 0.681, p = 0.01) in normotensive ADPKD patients. Conclusion: This pilot study demonstrates that UAGT levels tend to be elevated and are correlated with proteinuria and albuminuria in normotensive ADPKD patients during relatively early stages of the disease.